La disciplina y el consumo de sustancias psicoactivas en los estudiantes de básica superior de la Unidad Educativa Simón Rodríguez 2018 - Palma Alcívar, Luis Alexander (2018)
The present research focuses on the discipline and consumption of psychoactive substances in the students of Basic Superior of the Educational Unit "Simon Rodríguez" 2018. The family as the nucleus and main axis of society must be taken care of and given priority in any circumstance, parents have the responsibility to assume the commitment and provide care for their children in all the habits that society demands. The project proposal seeks help and benefits students who have problems of disciplinary behavior guiding them to feel safe and can express their dissatisfaction in their environment. Participation in this study is strictly voluntary, the information obtained will be confidential and will not be used for any other purpose than those of this research, your answers to the questionnaire and to the interview are anonymous. For the execution of the different areas of development, it has been considered for the area of psychological support its execution has been considered to be permanent during the year in which the project lasted in this first instance.